The role of specific checkpoint-induced S-phase transcripts in resistance to replicative stress. - Chaitali Dutta; Nicholas Rhind (PLoS ONE)
Checkpoint activation during S phase modulates transcription. In response to replication arrest, the fission yeast Cds1 checkpoint kinase maintains the normal S-phase transcriptional program by regulating MBF, the S-phase transcription factor. We show that similar regulation occurs in response to DNA damage during S-phase. We test the relative contributions to replication-stress resistance of transcriptional regulation and the two other major checkpoint functions: cell-cycle arrest and fork stabilization. We show that, although transcriptional regulation provides only modest resistance relative to fork stabilization, it contributes significantly to cell survival. Finally, we investigate the roles of two specific transcripts: mik1 and mrc1. These results demonstrate the general importance of checkpoint regulation of G1/S transcription in response to replicative stress and elucidate the specific roles of Mik1 and Mrc1 in the checkpoint.